2018
DOI: 10.1159/000486247
|View full text |Cite
|
Sign up to set email alerts
|

Acute In-Stent Thrombosis after Carotid Angioplasty and Stenting: A Case Report and Literature Review

Abstract: Background: Based on the results of a recent randomized controlled trial, carotid artery stenting (CAS) was regarded as a relatively safe, less invasive treatment of internal carotid artery stenosis. However, cerebral thromboembolic events are the most common complications of CAS. Especially acute stent thrombosis following CAS will be fatal without prompt diagnosis and revascularization. Case Report: We report a case of acute stent thrombosis in whom carotid revascularization was performed successfully via ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…For ACIST when the stent does not fully adhere to the blood vessel, a mechanical approach should be a feasible solution to the problem. Hu W. at al [11] used a protection filter deployed at the distal part of the stent and redilation of the stent performed with a balloon. Thus, carotid revascularization was performed successfully, proven by postprocedural angiogram.…”
Section: Discussionmentioning
confidence: 99%
“…For ACIST when the stent does not fully adhere to the blood vessel, a mechanical approach should be a feasible solution to the problem. Hu W. at al [11] used a protection filter deployed at the distal part of the stent and redilation of the stent performed with a balloon. Thus, carotid revascularization was performed successfully, proven by postprocedural angiogram.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors cause ACST, such as inadequate or early discontinuation of antiplatelet therapy, clopidogrel resistance, hypercoagulable state, soft plaque protrusion, local vessel dissection, vasospasm, and intimal injury [7][8][9] . Also, the stent morphology plays an important role in ACST 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Several of these factors (e.g., stent under-expansion, in which the stent does not fully adhere to the blood vessel 7 or balloon bursts 11 ), plaque protrusion 4 , and vasospasm can immediately cause ACST, but if promptly treated, can be resolved without any long-term defect to the nervous system. Other factors, such as inadequate or early discontinuation of antiplatelet therapy [12][13][14] , clopidogrel resistance, and hypercoagulable state 8 , may cause ACST a few days after the CAS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons causing ACST, such as inadequate antiplatelet therapy, early discontinuation of antiplatelet therapy, clopidogrel resistance, hypercoagulable state, soft plaque and its protrusion, local vessel dissection, vasospasm, intimal injury, and so on [6][7][8] . In one hand, a number of reasons, including cause of CAS (i.e., stent underexpansion, in which stent does not fully adhere to the blood vessel 6 , balloon burst 9 , etc. ), plaque protrusion 4 , and vasospasm that might immediately lead to ACST.…”
Section: Discussionmentioning
confidence: 99%
“…According to the review of 32 cases, 10 cases were found without reporting the relevant reasons caused disease 10,[12][13][14][15][16][17][18][19] , 11 cases due to CAS procedure 6,9,[19][20][21][22] , 2 cases due to antiplatelet resistance 18,23 , 3 cases due to hypercoagulable state 4,7,22 , 4 cases due to discontinuation of antiplatelet 11,13,24,25 , 1 case due to cardiac multiple embolism 13 , and 1 case remained unclear 26 . As we mentioned previously, the ACST caused by CAS is often timely resolved and patients may have a good prognosis, and that may be the most common reason as well.…”
Section: Discussionmentioning
confidence: 99%